2019
DOI: 10.1155/2019/3986964
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Crude and Wine-Processing Corni Fructus on Chemical Composition and Antidiabetic Effects

Abstract: Wine processing is a specialized technology which involves sautéing crude herbal medicine using Chinese rice wine. Herein, we identified the changes in chemical profiles and antidiabetic effects of Corni Fructus (CF) after wine processing in high-fat diet (HFD) streptozotocin- (STZ-) induced diabetic mice. A novel high-efficiency method for simultaneously quantifying gallic acid, 5-hydroxymethylfurfural, morroniside, loganin, sweroside, and cornuside by UPLC was developed, and validating crude and wine-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The chemical constituents of Corni Fructus include polysaccharides, iridoid glycosides, organic acids, tannins, esters, as well as aglycone [ 26 ]. The Crude Corni Fructus extract has been demonstrated to hold multiple pharmacological actions such as regulating immunity, anti-oxidation, hypoglycemic, anti-inflammation, anti-menopausal, neuroprotection, and bacteriostasis, which have thus been applied extensively in medicine and wellness product manufacturing [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Cornuside (7- O -Galloylsecologanol) is one of the major iridoid glycosides in Cornus officinalis (molecular structure is shown in Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of Corni Fructus include polysaccharides, iridoid glycosides, organic acids, tannins, esters, as well as aglycone [ 26 ]. The Crude Corni Fructus extract has been demonstrated to hold multiple pharmacological actions such as regulating immunity, anti-oxidation, hypoglycemic, anti-inflammation, anti-menopausal, neuroprotection, and bacteriostasis, which have thus been applied extensively in medicine and wellness product manufacturing [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Cornuside (7- O -Galloylsecologanol) is one of the major iridoid glycosides in Cornus officinalis (molecular structure is shown in Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…et Zucc (family Cornaceae) is generally expended as a nutritional food in the form of drinks and wine. It has been demonstrated that Corni Fructus has anti-inflammatory, 10 antioxidative, 11 antidiabetic, 12 immune regulatory, 13 antiatherosclerotic, 14 and antimicrobial 15 activities. Cornus iridoid glycoside (CIG) is a bioactive extract isolated from Corni Fructus; its beneficial role in focal cerebral ischemia has been verified to be closely involved in anti-inflammatory and anti-apoptotic activities.…”
Section: Introductionmentioning
confidence: 99%
“…; CO; family, Cornaceae) nourishes the liver and kidney and has a long history of treating diabetes. It is often prescribed in TCM prescriptions, such as Zan Yu Dan and Liuwei Dihuang Pill, treating spermatorrhea and reproductive disorders, respectively ( Park et al, 2015 ; Bi et al, 2019 ). Our previous studies have shown that Radix Rehmanniae and Cornus Officinalis (RR-CO) attenuated DM-induced testicular damage by regulating glucose metabolism, but the underlying mechanism needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%